PENGARUH BIAYA PERSONAL SELLING DAN SALES PROMOTION TERHADAP PENINGKATAN PENJUALAN CHANNEL GT (GENERAL TRADE) PADA PT. INDOFOOD FRITOLAY MAKMUR BALI - Ida Ayu Trisna Wijayanthi; Ida Bagus Ngurah Wimpascima; Doni Hendiarto (Forum Manajemen, 2022)
Indofood Fritolay Makmur is one of the largest snack companies inIndonesia and has several branch areas, one of which is in Bali. During the Covid-19pandemic, there are costs that are needed to produce good sales, namely personal sellingcosts and sales promotion costs to help increase sales in order to achieve monthlytargets. The purpose of this study is to determine the effect of personal selling costs andsales promotion costs partially and simultaneously on the sale of snack products on theGT (General Trade) channel, where this study will use multiple linear regression analysistechniques with the help of the SPSS version 21 for windows program. The results of thisstudy found that personal selling costs (X1) and sales promotion costs (X2) partially andsimultaneously had a significant effect on sales (Y) in PT. Indofood Fritolay MakmurChannel General Trade Bali. While the most dominant variable that has an effect onsales is the personal selling cost variable () because it has a Beta coefficient value of0.646 compared to the value of the sales promotion cost coefficient () which is only0.453.Based on the results of the determination test, an R2 value of 0.669 is obtained,which means that the amount of contribution of the personal selling cost variable (X1)and sales promotion cost (X2) is 66.9% while 33.1% is influenced by other variables thatare not researched in this study.